Pelatihan Pembuatan Blog Untuk Meningkatkan Skill TIK Anak Yatim Yayasan Dulur Salembur - Hartanti, Dian; Noe’man, Achmad (Journal Of Computer Science Contributions (JUCOSCO), 2023)
Technological advances are currently growing rapidly, because most human activities cannot be separated from information technology. The need for information has led to an increase in the need for blogs. The problem that occurs is that there is still a lack of experts who have mastery in making interesting blogs, this causes little information to be obtained through blogs and business opportunities which are inversely proportional to the community's need for blogs. The orphans at the Salembur orphanage belong to the poor category. poor economic level so it deserves help. Therefore, this blog creation training is suitable to be taught to junior high school orphans. The training starts with creating an email followed by creating a blog using wordpress.com. It is hoped that this skill can help orphans to be able to take advantage of blogging expertise as a source of additional income in the form of blogging services. In addition, the results of this training aim to help inform donors about the profile of the YDS Yatim Foundation by creating a blog profile in the form of information on the activities of the orphanage and other information with the hope that it will increase the number of donors who will participate in the YDS orphanage.